INTEGRATION OF GENERATIVE AI INTO PERSONALIZED EDUCATIONAL PLATFORMS TO IMPROVE LEARNING EFFECTIVENESS - Mariia Gogoleva (Web of Journals Publishing, 2025)
This article examines the theoretical, technological, and practical aspects of integrating generative artificial intelligence ( GenAI ) into personalized educational platforms. Based on an analysis of current research on intelligent learning systems and large-scale language models, the potential of generative technologies for improving learning effectiveness through adaptive delivery of materials, automatic content generation, personalized feedback, and support for metacognitive strategies is assessed.
Keywords: Generative artificial intelligence, large language models, personalized learning, intelligent learning systems, adaptive educational platforms, automatic content generation.